The Work of Sharing - Annette Arlander; Bruce Barton; Johanna Householder; Michelle Man (Performance Philosophy)
This multimedia essay is describing or rather demonstrating one attempt at dealing with the problem how to discuss performance in the mode of performance, based on the presentation at the Performance Philosophy conference in Helsinki in June 2022. There we—four members of the Artistic Research Working Group (ARWG) of Performance Studies international (PSi)—tried to present and demonstrate in a miniature form one of the methods for sharing we have explored in the working group, and to do it in a hybrid format, with two performers in the room and two performers present via zoom. The three phases of the method (perform–respond–expand) were performed by three members of the group and condensed into three minutes of prerecorded material per person at each stage. An extract of our preparatory discussions on zoom is added to the essay, as well as a link to the working group archive or blog.